A Call to Action for a Comprehensive Earthquake Education Policy in Nepal - Hetényi, György; Subedi, Shiba (Seismica, 2023)
Earthquakes in Nepal are among the most damaging natural hazards, claiming many lives and causing more widespread destruction than any other natural hazard. Yet, due to other difficulties and challenges, earthquakes are at the forefront of people’s attention only after major events, such as the 1934 or 2015 earthquakes. As a result, current preparedness of the population to earthquakes is far below the optimal level. This calls for an immediate and widespread educational effort to increase awareness and to raise the current young generation responsibly. After describing the current status of earthquake education at various school levels in Nepal, we here propose a series of actions to undertake towards an official education policy, starting from full openness and use of languages, via coordination and teacher's training, to the content, frequency and style of curriculum. We conclude on a timeline of actions, which have various lengths but should start today. We hope that by sharing our researcher and educational experience and thoughts, the actual preparation of the earthquake education policy for Nepal will start being developed under a dedicated team. Elements of the proposal presented here can be used and adapted to other regions at risk around the world.